Seasonal Changes in Nitrate Uptake Efficiency in Young Potted Citrus Trees - Martínez-Alcántara, Belén; Quinones, Ana; Primo-Millo, Eduardo; Legaz, Francisco (Canadian Center of Science and Education, 2020)
Fertilizer isotope labelling (15N) of young Lane Late potted orange trees with differential N rates at three phenological periods (end of flowering, fruit set and fruit growth) was used to determine patterns of N uptake response and N efficiency (NUE) along the growing cycle. In a first experiment trees were fed with a saturating N solution in order to determine seasonal variations in N requirements. The second experiment tested four N rates which were equal to (N1), two (N2), three (N3) and four-fold (N4) the N requirements at each period. Increasing N rate diminished NUE being the decrease more acute at flowering as a consequence of the lower response in N uptake to increased N supply in this period. Theoretical NUE corresponding to a fertilizer rate that fulfills plant requirements in each period was calculated, being highest at the end of fruit set period (72%), which contrasted with the value obtained for flowering (28%), when potential nitrogen leaching reached therefore its maximum (71%).